Preparation method of oxygen-deficient tungsten oxide WO2.72 nanospheres with photodegradation adsorption performance
By dissolving urea and tungsten chloride in anhydrous ethanol, magnetic stirring and hydrothermal reaction, combined with ultrasonic dispersion and lyophilization treatment, WO2.72 nanospheres that are not easily agglomerated were prepared, and the oxygen-deficient tungsten oxide WO2.72 synthesis was solved by solving the synthesis of oxygen-deficient tungsten oxide WO2.72 The agglomeration problem during the process improves its adsorption and photodegradation properties, simplifies the production process and reduces costs.
Patent Information
- Application Number
- CN202411272212.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-11
AI Technical Summary
In the prior art, oxygen-deficient tungsten oxide WO2.72 is prone to agglomeration during the synthesis process, which limits the performance of its physical functional characteristics. The existing methods are complex and costly, making it difficult to achieve uniform mixing and stability, which affects the photocatalytic performance. .
By dissolving urea and tungsten chloride in anhydrous ethanol, magnetic stirring and hydrothermal reactions were carried out, combined with ultrasonic dispersion and lyophilization, precisely controlling the synthesis conditions, WO2.72 nanospheres that are not easily agglomerated were prepared to improve their adsorption and photodegradation. performance.
The high dispersion and photocatalytic activity of WO2.72 are achieved, which significantly improves the degradation rate of methylene blue, simplifies the production process, reduces costs, and supports the recycling of materials, improving application efficiency.
Smart Images

Figure CN119140086A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis technology, and specifically relates to oxygen-deficient tungsten oxide WO with photodegradation adsorption performance. 2.72 Preparation method of nanospheres. Background Art
[0002] Purple tungsten (oxygen-deficient tungsten oxide), (chemical formula WO 2.72 ) has excellent electrochemical properties and is suitable for use as a negative electrode material for lithium batteries. Its high theoretical specific capacity, fast ion transport rate and large porosity allow it to extend the battery life while also improving charge and discharge performance.
[0003] In addition, purple tungsten has become an important raw material for preparing dimming glass due to its good electrochromic and photochromic effects, as well as its strong absorption of electromagnetic waves, which can give glass the function of changing color. At the same time, purple tungsten has excellent optical properties and strong absorption capacity in the near-infrared light region, and can be used to prepare near-infrared photothermal diagnostic and therapeutic drugs, which has great application value in cancer treatment. In addition, purple tungsten also has excellent gas sensitivity and catalytic properties, which can accelerate the rate of chemical reactions and can be used for the degradation of related fuels; in general, purple tungsten oxide has a variety of unique properties and broad application prospects, and plays an important role in many fields.
[0004] At present, there are also related purple tungsten for degrading dyes. For example, the patent with patent publication number CN 102985178A discloses a method for preparing copper-modified purple tungsten photocatalyst, which uses a solvent (preferably an organic solvent such as alcohol) to mechanically grind copper ion-modified tungsten oxide particles; then the dispersion of the obtained ground particles is contacted with oxygen or ozone to obtain the catalyst. The method aims to improve the photocatalytic activity, especially the activity under visible light. The dispersion after drying can obtain a photocatalyst powder, which has a diffuse reflectance of 75% or more when measured at a wavelength of 700nm, and its catalytic activity under visible light conditions is improved; however, the copper-modified purple tungsten photocatalyst prepared by this method is difficult to achieve uniform mixing at the molecular level, which may lead to excessively high or low local copper concentration, affecting the overall catalytic performance and stability; and the need for additional oxidation treatment not only increases the process complexity and production cost, but also may introduce additional impurities or cause unnecessary damage to the product structure. At the same time, excessive grinding may cause lattice distortion or amorphization, reducing the photocatalytic activity and selectivity of the material.
[0005] In addition, patent number CN 104785275 A discloses a method for the dispersion of copper ion modified tungsten oxide photocatalyst, which uses a solution method to synthesize copper-doped violet tungsten powder in one step. The method aims to introduce defect positions by doping with copper at an appropriate concentration, affecting the recombination of electrons and holes, thereby improving the photocatalytic effect; however, the method requires a high reaction temperature, and the high temperature of 200°C not only consumes a lot of energy, but may also cause the reaction to run away or the product structure to be unstable; at the same time, the needle-like structure finally obtained has a small specific surface area and is easy to agglomerate, which is not conducive to the catalytic reaction; in addition, the diameter of the catalyst dispersion obtained is 30-200nm, and the wide distribution range of its diameter will lead to unstable performance.
[0006] In addition, in the prior art, for WO 2.72 It is usually prepared by a hydrothermal method, which involves using a tungsten source and ethanol (or alcohols) to react at a specific time and temperature. However, this method has a major problem: the synthesized WO 2.72 The product is prone to agglomeration, which severely limits its physical functional properties, such as adsorption, photodegradation and photocatalysis. To overcome this limitation, it is usually necessary to convert WO 2.72 It can only play a specific functional property when combined with other substances to form a composite material. 2.72 There are still flaws.
[0007] How to prepare WO that is not prone to agglomeration and has excellent adsorption and photodegradation properties for fuels 2.72 It is still an urgent problem to be solved. Summary of the invention
[0008] In order to solve the above technical problems, the present invention discloses an oxygen-deficient tungsten oxide WO having photodegradation adsorption performance. 2.72 The preparation method of nanospheres, the present invention prepares WO by precisely controlling the synthesis conditions 2.72 , synthesized WO 2.72 The degree of agglomeration of the product can be significantly reduced, thereby effectively exploring its physical functional properties. The WO prepared by the present invention 2.72 It can be directly applied to environmental governance and energy conversion without relying on composite materials, thereby simplifying the production process, reducing costs, and improving the application efficiency of materials; in particular, the WO synthesized by the present invention 2.72 It exhibits excellent adsorption and photodegradation properties for dyes.
[0009] In order to achieve the above technical effects, the present invention is implemented by the following technical scheme: oxygen-deficient tungsten oxide WO with photodegradation adsorption performance 2.72 The method for preparing nanospheres comprises the following steps:
[0010] S1: dissolving the raw materials urea and tungsten chloride in anhydrous ethanol at a ratio of 0.08-0.1:0.8-1, and subjecting the mixed solution to magnetic stirring at 10°C-40°C until the raw materials are completely dissolved in the anhydrous ethanol, and then titrating the dissolved solution with deionized water and continuing to subject the mixed solution to magnetic stirring until the mixed solution becomes colorless and transparent;
[0011] S2: The mixed solution obtained in S1 is quickly poured into a polytetrafluoroethylene liner and then transferred into a hydrothermal reactor. The sealed reactor is placed in a drying oven and dried and kept warm for a period of time, thereby performing a hydrothermal reaction to synthesize the product;
[0012] S3: After natural cooling, the precipitate is ultrasonically dispersed and centrifuged with deionized water. The washed product is dispersed in deionized water to form a dispersion. The dispersion is placed in a freeze dryer to remove the deionized water to directly obtain a highly dispersible blue-gray WO 2.72 ;
[0013] Furthermore, during the magnetic stirring in S1, the magnetic stirring rate is 100-500 rpm, the stirring time is 2-6 hours, the amount of deionized water added is 0.5-1.5 parts, and the amount of ethanol added is 60-100 parts;
[0014] Furthermore, during the magnetic stirring in S1, the magnetic stirring rate was 300 rpm, the stirring time was 3 hours, the amount of deionized water added was 0.9 parts, and the amount of ethanol added was 80 parts;
[0015] Furthermore, during the drying in S2, the drying temperature is 100-250° C. and the heat preservation time is 8-30 hours;
[0016] Furthermore, during the drying in S2, the drying temperature is 180° C. and the heat preservation time is 18 hours;
[0017] Furthermore, in S3, the ultrasonic dispersion time is 5-20 min, the number of ultrasonications is 5-10 times, the centrifuge speed is 6000-10000 rpm, the number of centrifugations is 5-10 times, the temperature of the freeze dryer is -60°C-0°C, the air pressure in the freeze dryer is 0.1-5 Pa, and the freeze drying time is 10-48 hours.
[0018] The beneficial effects of the present invention are:
[0019] In the preparation process of the method of the present invention, urea is first used to provide ammonium cations, which are embedded in tungsten oxide to form a non-stoichiometric compound ammonium tungsten bronze (NH4). 0.33 WO 3, The deionized water in the mixed solution provides OH - The cation captures and precipitates the ammonia cation, causing the valence state of W to change from W 6+ Restore to W 5+At the same time, in the synthesis process, alcohols are used as solvents, which provide 2.72 The desired reaction medium, on the other hand, controls the growth and morphology of the product through its interaction with urea and deionized water to synthesize the final product WO 2.72 WO synthesized by the above method 2.72 It not only solves the problem of traditional synthetic WO 2.72 The agglomeration problem of the product was solved, and the product morphology and size were precisely regulated by precisely controlling the synthesis conditions, which improved the adsorption and photodegradation properties of the product. The degradation rate of methylene blue dye was over 99%.
[0020] In addition, the WO prepared by the present invention 2.72 It can be directly applied to environmental governance and energy conversion without relying on composite materials, and the WO 2.72 It can be prepared again as WO before use 2.72, It can be recycled. This method not only simplifies the production process, but also effectively reduces the cost through recycling under simple conditions and improves the application efficiency of the material. It has important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings required for describing the embodiment are briefly introduced below.
[0022] Figure 1 The present invention synthesizes WO 2.72 Flowchart of nanospheres;
[0023] Figure 2 is the XRD pattern of the sample prepared by the preparation method of the present invention;
[0024] Figure 3 It is a SEM picture of the sample prepared by the preparation method of the present invention.
[0025] Figure 4 It is a TEM image of the sample prepared by the preparation method of the present invention.
[0026] Figure 5 This is an XPS graph of a sample prepared by the preparation method of the present invention, where a is oxygen-deficient tungsten oxide WO 2.72 Full spectrum, b is oxygen-deficient tungsten oxide WO 2.72 Oxygen element spectrum, c is oxygen defect tungsten oxide WO 2.72 Elemental spectrum of tungsten in .
[0027] Figure 6The present invention is a degradation rate diagram of the sample prepared by the preparation method of the present invention for photodegradation adsorption of methylene blue under different concentrations and lighting conditions; in the figure, d is a degradation rate diagram when the concentration of the methylene blue solution is 10 ml / L under the conditions of dark room, laboratory lighting, and xenon lamp lighting; e is a degradation rate diagram when the concentration of the methylene blue solution is 30 ml / L under the conditions of dark room, laboratory lighting, and xenon lamp lighting; f is a degradation rate diagram when the concentration of the methylene blue solution is 50 ml / L under the conditions of dark room, laboratory lighting, and xenon lamp lighting.
[0028] Figure 7 The sample prepared by the preparation method of the present invention is subjected to photodegradation and adsorption of methylene blue, and the solution after photodegradation and adsorption is taken at different times, and then the transparent clear solution is taken by centrifugation to obtain UV-Vis-IR graph; the darkroom is shown in Figure g, the laboratory lighting is shown in Figure h, and the xenon lamp lighting is shown in Figure i.
[0029] Figure 8 The SEM images of the samples prepared by the preparation method of the present invention are obtained by titrating different amounts of deionized water.
[0030] Fig. 9 The UV-Vis-IR graph of the optical properties of the samples prepared by the preparation method of the present invention is obtained by dispersing equal amounts of samples obtained by titrating different amounts of deionized water in water and measuring the UV-Vis-IR graph of the optical properties of the samples.
[0031] Fig.10 The present invention is a methylene blue removal rate bar graph of samples prepared by the preparation method of the present invention, obtained by titrating different amounts of deionized water, and performing a 2-hour photodegradation adsorption experiment on 100 ml of a 50 mg / L methylene blue solution.
[0032] Fig.11 The degradation rate graph of the samples prepared by other preparation methods was subjected to a 2-hour photodegradation adsorption tracking experiment on 100 ml of 10 mg / L, 30 mg / L and 50 mg / L methylene blue solutions under xenon lamp irradiation.
[0033] Fig.12 50 mg of the sample prepared by the preparation method of the present invention is respectively used for 100 ml of 10 mg / L, 30 mg / L and 50 mg / L methylene blue solutions, and a removal rate diagram of a methylene blue removal tracking experiment is performed for 2 hours in a dark room.
[0034] Fig.13 FTIR graph of the sample prepared by the preparation method of the present invention. DETAILED DESCRIPTION
[0035] Example 1
[0036] Oxygen-deficient tungsten oxide WO with photodegradation and adsorption properties 2.72The preparation method of nanospheres specifically comprises the following steps by mass:
[0037] S1: Weigh 0.095g of urea and 0.95g of tungsten chloride into a 100ml beaker, drop 0.5-1.5ml of deionized water, add 80ml of anhydrous ethanol, stir with a magnetic stirrer at a stirring rate of 300rpm and a stirring temperature of 25°C for 3 hours until the solution becomes a transparent colorless liquid;
[0038] S2: Pour the mixed solution obtained in S1 into a 100 ml polytetrafluoroethylene liner, place the liner in a reactor, and perform a hydrothermal reaction in a drying oven at a reaction temperature of 180°C for 18 hours;
[0039] S3: After the reaction in S2 is complete, the temperature is naturally lowered to room temperature, the supernatant is extracted, and the blue-gray nano-product WO on the inner substrate is rinsed with 50 ml of deionized water. 2.72 Place it in a 100 ml beaker and perform ultrasonic dispersion for 10 minutes. Centrifuge the dispersed liquid for 3 minutes at a centrifugal rate of 8000 rpm. Disperse the centrifuged product in 50 ml of deionized water. Perform the ultrasonic and centrifugal cycles for 3 times. Freeze-dry the collected product at -45 °C, at a freeze-drying pressure of 0.5 Pa, and for 36 hours.
[0040] After the above experimental process, Figure 1 As shown, blue-grey oxygen-deficient tungsten oxide WO is finally obtained. 2.72 ; Figure 2 is the XRD pattern of the prepared sample. Figure 2 It can be seen that the WO synthesized by this patent 2.72 It is a single phase with no other substance peaks; Figure 3 and Figure 4 is the SEM image of the sample, showing the morphology, degree of agglomeration and size of the sample. Figure 3 and Figure 4 It can be seen that the blue-grey oxygen-deficient tungsten oxide WO prepared by this method 2.72 It is not agglomerated together, but in dispersed particles. The specific surface area of the dispersed particles will be significantly increased. The dispersed particles are not easy to precipitate or stratify during storage and use. They can maintain the uniformity and stability of the material, excellent catalytic performance, higher electrochromic performance, better optical properties, and higher theoretical specific capacity and ion transport rate.
[0041] Example 2
[0042] The blue-grey oxygen-deficient tungsten oxide WO prepared by the preparation method in Example 1 2.72The photodegradation adsorption performance test was carried out to further verify its actual degradation situation. The specific process is as follows:
[0043] Weigh 50 mg of the blue-gray oxygen-deficient tungsten oxide WO obtained by the above preparation process 2.72 Participate in each photodegradation adsorption performance test. The test light environment is divided into dark room, laboratory lighting and xenon lamp lighting. 50 mg of sample is weighed and added to 100 ml of methylene blue solution of different concentrations (10 mg / L, 30 mg / L, 50 mg / L). 4 ml of the dispersion is extracted at different time points during the photodegradation process for centrifugation. The centrifugal speed is 10000 rpm and the centrifugal time is 2 minutes. After centrifugation, the transparent clear solution is taken for optical property detection to determine the residual amount of methylene blue. The specific test results are as follows: Figure 6 , 7 As shown in the figure, from the analysis of the test results, it can be seen that for 100ml of 10mg / L and 30mg / L methylene blue aqueous solutions, no matter the lighting conditions are darkroom, laboratory lighting or xenon lamp lighting, the blue-gray oxygen-deficient tungsten oxide WO 2.72 The removal rate of methylene blue within 5 minutes is more than 99%; for a 50 mg / L methylene blue aqueous solution, under dark room and laboratory lighting conditions, the removal rates of methylene blue within 2 hours are 83% and 85% respectively, and under xenon lamp lighting, the removal rate of methylene blue within 1 hour is more than 99%. This further illustrates the blue-gray oxygen-deficient tungsten oxide WO prepared by the present invention. 2.72 , improving the adsorption and photodegradation adsorption performance of the product; in addition, the WO prepared by the present invention 2.72 It can be directly applied to environmental governance and energy conversion without relying on composite materials, thereby simplifying the production process, reducing costs, and improving the application efficiency of materials.
[0044] Example 3
[0045] Based on the preparation method in Example 1, it was found during the synthesis experiment that the amount of deionized water in the mixed solution is very sensitive to the control of the nano characteristics (agglomeration degree, morphology, particle size) of the nano product, and the change of the nano characteristics can directly affect the optical properties of the nano product, thereby changing the photodegradation adsorption performance of the nano product in removing methylene blue;
[0046] In order to further verify the above process, specifically: oxygen-deficient tungsten oxide WO with photodegradation adsorption performance 2.72 The preparation method of nanospheres includes the following steps according to mass: dropping different amounts of deionized water 0.7ml, 0.8ml, 0.9ml, 1.0ml to obtain oxygen-deficient tungsten oxide WO with different nano characteristics 2.72 sample):
[0047] S1: Weigh 0.095g of urea and 0.95g of tungsten chloride into a 100ml beaker, drop 0.7ml of deionized water, add 80ml of anhydrous ethanol, stir with a magnetic stirrer at a stirring rate of 300rpm and a stirring temperature of 25°C for 3 hours until the solution becomes a transparent colorless liquid;
[0048] S2: Pour the mixed solution obtained in S1 into a 100 ml polytetrafluoroethylene liner, place the liner in a reactor, and perform a hydrothermal reaction in a drying oven at a reaction temperature of 180°C for 18 hours;
[0049] S3: After the reaction in S2 is completed, the temperature is naturally cooled to room temperature, the upper clear liquid is extracted, and the blue-gray nano product WO on the inner substrate is rinsed with 50 ml of deionized water. 2.72 Place the mixture in a 100 ml beaker and perform ultrasonic dispersion for 10 min. Centrifuge the dispersed solution for 3 min at a rate of 8000 rpm. Disperse the product obtained by centrifugation in 50 ml of deionized water. Perform the ultrasonic and centrifugal steps for 3 times. The collected product is freeze-dried at a temperature of -45 °C, a pressure of 0.5 Pa, and a time of 36 hours to obtain the first sample.
[0050] Similarly, S1: weigh 0.095 g of urea and 0.95 g of tungsten chloride into a 100 ml beaker, drop 0.8 ml of deionized water, add 80 ml of anhydrous ethanol, stir with a magnetic stirrer at a stirring rate of 300 rpm and a stirring temperature of 25 °C for 3 hours until the solution becomes a transparent colorless liquid;
[0051] S2: Pour the mixed solution obtained in S1 into a 100 ml polytetrafluoroethylene liner, place the liner in a reactor, and perform a hydrothermal reaction in a drying oven at a reaction temperature of 180°C for 18 hours;
[0052] S3: After the reaction in S2 is completed, the temperature is naturally cooled to room temperature, the upper clear liquid is extracted, and the blue-gray nano product WO on the inner substrate is rinsed with 50 ml of deionized water. 2.72 Place the mixture in a 100 ml beaker and perform ultrasonic dispersion for 10 min. Centrifuge the dispersed solution for 3 min at a rate of 8000 rpm. Disperse the product obtained by centrifugation in 50 ml of deionized water. Perform the ultrasonic and centrifugal steps for 3 times. Freeze-dry the product collected at -45 °C at a pressure of 0.5 Pa and for 36 hours to obtain a second sample.
[0053] In addition, in step 1 of the above steps, 0.9 ml and 1.0 ml of deionized water were titrated respectively, and the rest of the process was the same to obtain the third and fourth samples respectively;
[0054] The SEM images of the four samples mentioned above are as follows: Figure 8 As shown, Figure a shows that the amount of deionized water used in the synthesis of the sample is 0.7ml; Figure b shows that the amount of deionized water used in the synthesis of the sample is 0.8ml; Figure c shows that the amount of deionized water used in the synthesis is 0.9ml; Figure d shows that the amount of deionized water used in the synthesis is 1.0ml. It can be seen from the figure that when the deionized water titration is 0.7ml and 0.8ml, the degree of agglomeration of the nanoparticles of the sample is very serious, the morphology of the nanoparticles is not obvious, and the particle size of the nanoparticles is in the range of 10nm to 80nm. When the deionized water titration is 0.9ml, the dispersion of the sample nanoparticles is significant, the morphology of the nanoparticles is nanospheres composed of nanoneedles, and the particle size of the nanoparticles is in the range of 50nm to 150nm. When the deionized water titration is 1.0ml, the dispersion of the sample nanoparticles is significant, and the morphology of the nanoparticles is nanospheres composed of nanoneedles. , the particle size of the nanoparticles is in the range of 150nm to 300nm; when the amount of deionized water is small (0.7ml and 0.8ml), although the particle size of the synthesized nanoparticle samples is small, the degree of agglomeration is serious and the morphology is not obvious. When the amount of deionized water is large (1.0ml), although the degree of agglomeration of the synthesized nanosamples is significantly reduced and they have a nanosphere morphology composed of nanoneedles, the particle size is too large. When the deionized water titration is 0.9ml, the nano characteristics of the nanosamples in terms of dispersibility, morphology and particle size are more suitable without obvious defects.
[0055] In addition, if Fig. 9 The optical properties of the UV-Vis-IR graph show that the oxygen-deficient tungsten oxide WO synthesized by titrating 0.7ml, 0.8ml, and 1.0ml of deionized water during the synthesis process 2.72 The sample has no absorption peak in the visible light band (380nm~720nm), and the oxygen-deficient tungsten oxide WO synthesized by titrating 0.9ml of deionized water during the synthesis process 2.72 The sample has an absorption peak in the visible light band, which will increase the oxygen defect tungsten oxide WO 2.72 The sample's photodegradation adsorption performance for methylene blue; this comparison can also further illustrate that it has a significant effect on the photodegradation adsorption performance of methylene blue when titrating 0.9 ml of deionized water.
[0056] Example 4
[0057] In this example, based on the titration of different amounts of deionized water in Example 3, the photodegradation adsorption performance of the sample was further tested. The specific steps and process of the test were the same as those described in Example 2, except that the content of deionized water used was different. The specific results are as follows: Fig.10 As shown, oxygen-deficient tungsten oxide WO with different nano features and optical properties was synthesized by titrating different amounts of deionized water (0.7 ml, 0.8 ml, 0.9 ml, 1.0 ml). 2.72 50 mg of each sample was dispersed in 100 ml of 50 mg / L methylene blue solution. The dispersion was subjected to a photodegradation experiment for 1 hour under xenon lamp illumination. During this period, the dispersion was sampled at intervals to perform a photodegradation experiment on methylene blue. The removal rate of methylene blue by photodegradation was shown in the bar graph (see Figure 2). Fig.10 ), Fig.10 The lighting conditions in the figure are xenon lamp lighting. The purple column is a sample with a titration volume of 0.7 ml of deionized water, the green column is a sample with a titration volume of 0.8 ml of deionized water, the pink column is a sample with a titration volume of 0.9 ml of deionized water, and the blue column is a sample with a titration volume of 1.0 ml of deionized water. The synthesized oxygen-deficient tungsten oxide WO was titrated with 0.7 ml, 0.8 ml, and 1.0 ml of deionized water during the synthesis process. 2.72 The removal rates of methylene blue by the samples within 1 hour were all less than 70%, namely 49%, 52% and 65% respectively. 2.72 The removal rate of methylene blue by the sample reached more than 99% within 1 hour.
[0058] In summary, in the synthesis of oxygen-deficient tungsten oxide WO 2.72 In the experiment, the tungsten oxide WO prepared by this method 2.72 It has very good photodegradation adsorption performance. When the content of deionized water is 0.9 ml, it has more excellent photodegradation adsorption performance. When used as a catalytic degradation agent, it is a better choice to select 0.9 ml for titration.
[0059] In this example, in order to highlight the oxygen defect tungsten oxide WO 2.72 The superiority of the photodegradation adsorption performance of the nanospheres was compared with other materials in a 2-hour methylene blue solution photodegradation adsorption tracking experiment. The photodegradation adsorption experiment of other material samples was carried out under the illumination of a xenon lamp. The oxygen-deficient tungsten oxide WO synthesized by this method 2.72The nanosphere samples were subjected to photodegradation adsorption. The illumination conditions used in the experiment were dark room (no light). 50 mg of the sample was taken, and the photodegradation adsorption experiment was carried out on 100 ml of 10 mg / L, 30 mg / L and 50 mg / L methylene blue, respectively. The dispersion, sampling and detection steps were consistent with Example 2, and no further explanation is given here.
[0060] For other material samples, the photodegradation adsorption methylene blue removal rate diagram was obtained, such as Fig.11 As shown, the lighting condition is xenon lamp irradiation, the dispersion is stirred for 2 hours, and the dispersion is sampled continuously at intervals to measure the removal rate of methylene blue in different concentrations of methylene blue at different times. The yellow column corresponds to 10 mg / L methylene blue solution, the sky blue column corresponds to 30 mg / L methylene blue solution, and the pink column corresponds to 50 mg / L methylene blue solution. It can be seen from the figure that the maximum removal rates of methylene blue in solutions of different concentrations of other material samples under xenon lamp irradiation within 2 hours are 63%, 52% and 41% respectively, corresponding to concentrations of 10 mg / L, 30 mg / L and 50 mg / L;
[0061] Fig.12 The figure is a graph of the removal rate of methylene blue by photodegradation adsorption of the samples prepared in the present invention, and the lighting condition is a dark room (no light), wherein the yellow column corresponds to a 10 mg / L methylene blue solution, the blue column corresponds to a 30 mg / L methylene blue solution, and the red column corresponds to a 50 mg / L methylene blue solution. 2.72 In a dark room (without light), the removal rate of methylene blue by the nanosphere sample within 2 hours can reach more than 99% (within 5 minutes), more than 99% (within 5 minutes) and 80% (within 1 hour) respectively, corresponding to the concentration of 10mg / L, 30mg / L and 50mg / L. From the three aspects of light conditions, removal rate and removal time, the oxygen-deficient tungsten oxide WO synthesized by this method 2.72 The nanosphere samples have significant advantages in the photodegradation adsorption performance of removing methylene blue.
[0062] The reasons can be found based on the FIRT diagram analysis, specifically, Fig.13 As shown, at 605cm -1 and 803cm -1 The two correspond to WO 2.72 The bridge bond WOW vibration and oxygen vacancy induced WO vibration are due to freeze drying on WO 2.72 There are water molecules and hydroxyl groups (OH) on the surface, which appear at 1642 cm -1 and 3443cm -1 These water molecules and hydroxyl groups can provide more active sites, which will help to enhance the WO 2.72The photocatalytic activity of methylene blue can more efficiently generate free radicals with strong oxidative ability (such as ·OH and ·O2 - ), these free radicals can effectively attack and decompose organic pollutants; at the same time, water molecules and hydroxyl groups are polar molecules, which can interact with the polar groups in the methylene blue molecules through hydrogen bonds, enhancing the WO 2.72 Adsorption capacity for methylene blue and photodegradation products.
[0063] Example 5
[0064] In this embodiment, the oxygen-deficient tungsten oxide WO with good performance obtained in Example 3 is specifically provided. 2.72 Treatment of water sources contaminated by methylene blue and treatment of used WO 2.72 The desorption and recycling method specifically comprises the following steps:
[0065] S1: First determine the concentration of methylene blue in the contaminated water source by spectrophotometer. If it is less than 50ml / L, use WO 2.72 The concentration in the solution is 25 mg / L. If it is higher than 50 ml / L, WO 2.72 The concentration in the solution is 50 mg / L. The corresponding WO is taken according to the amount of sewage to be treated. 2.72 The amount.
[0066] S2: WO determined according to S1 2.72 The amount is weighed, dispersed in deionized water, poured into a nanofiltration membrane for sealing, and then put into a water source pool contaminated with methylene blue.
[0067] Generally, water samples are collected every 2.5 hours during the day (8:00-18:00) and every 5 hours at night (20:00-6:00). The sampling interval can be adjusted according to the concentration change of methylene blue. The absorbance corresponding to the characteristic wavelength is measured by a spectrophotometer until the concentration of methylene blue in the water source drops to the concentration of the added WO 2.72 If the limit value meets the discharge requirements, the adsorption and photodegradation of methylene blue will be stopped. If it does not meet the requirements, the WO2-containing solution will be added to the polluted water source. 2.72 Nanofiltration membranes for deionized water dispersions.
[0068] S3: Based on S2, the used WO 2.72 Desorption and recovery treatment is performed; the amount of used WO2.72 desorbed each time does not exceed 3g, and the amount of all solvents used is 100ml.
[0069] Desorption recovery is divided into 3 steps:
[0070] 1) First, remove no more than 3g of used WO 2.72 Place in 100 ml of deionized water for 30 min ultrasonic dispersion, and then magnetically stir for 4 h to make WO 2.72 The attached materials on WO were dissolved in deionized water. 2.72 Desorption was performed, and the above steps were repeated twice, followed by centrifugation at 8000 rpm, and the aqueous solution after centrifugation was collected, and WO was recovered at the same time. 2.72 ;
[0071] 2) Next, the WO recovered by centrifugation 2.72 Disperse it again in 100 ml of deionized water and add 50 times of sodium chloride to make the sodium ions react with WO 2.72 The attached substances on the WO are exchanged by ions, and the replaced adsorbents are dissolved in deionized water to achieve the purpose of WO 2.72 Continuous desorption, where the desorption steps are: ultrasonic dispersion, magnetic stirring, centrifugal recovery. The specific parameters are the same as above, the number of cycles is 2, and the solution after centrifugation is continuously collected and WO is recovered. 2.72 ;
[0072] 3) Again, the WO recovered by centrifugation 2.72 Dispersed in 100 ml of organic solvent ethanol, ethanol to make WO 2.72 Dissolve the attachments on WO 2.72 Further desorption is performed, wherein the desorption steps are as above and will not be repeated here.
[0073] After the desorption step, the solution collected after centrifugation is finally heated to remove the solvent, and the obtained methylene blue and the photodegraded substances are calcined to remove the adsorbent; the desorbed WO 2.72 Dispersed in deionized water and freeze-dried. 2.72 It is used again to treat water sources polluted by methylene blue. It can not only adsorb and remove polluted water sources, but also remove them with high efficiency. Under conventional test conditions, it can achieve high-efficiency removal, up to 99% or more; it can also be recycled, which can save resources to a great extent and realize the recycling of resources.
[0074] Based on the above examples 1-4, the oxygen-deficient tungsten oxide WO with photodegradation adsorption performance synthesized by the present invention is 2.72 The oxygen-deficient tungsten oxide WO synthesized by the method of the present invention is prepared by controlling the growth and morphology of the product through the interaction of the raw material tungsten chloride with urea and deionized water by hydrothermal synthesis. 2.72 It not only solves the problem of traditionally synthesized oxygen-deficient tungsten oxide WO 2.72The agglomeration problem is solved, and by precisely controlling the synthesis conditions, the morphology and size of the product are precisely regulated, and the adsorption and photodegradation properties of the product are improved; in order to make the synthesized oxygen-deficient tungsten oxide WO 2.72 The excellent nano features of the synthesis are maintained in terms of agglomeration degree, morphology and dispersibility, so as to maximize the adsorption and photodegradation properties of the product. This method abandons the conventional drying and grinding method to collect WO 2.72 Make WO 2.72 Agglomeration increased, and WO was collected by freeze-drying 2.72 To achieve WO 2.72 The retention and improvement of various excellent properties; the WO synthesized by this method with significant adsorption and photodegradation properties 2.72 The repeated recycling and thus reducing the use cost is crucial to its practical application prospects. In this method, WO is desorbed in deionized water, sodium chloride solution and ethanol by designing desorption steps. 2.72 The adsorbed methylene blue and photodegraded substances are desorbed layer by layer, and finally the desorbed WO 2.72 It maintains the original surface properties and nano features, thereby maintaining good adsorption and photodegradation properties, and can be directly applied to environmental governance and energy conversion without relying on composite materials, thereby simplifying the production process, reducing costs, and improving the application efficiency of materials. It has important scientific significance and application value.
[0075] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only the specific implementation methods described.
Claims
1. Oxygen-deficient tungsten oxide WO with photodegradation adsorption performance 2.72 The method for preparing nanospheres is characterized in that: The following steps are involved: S1: dissolving the raw materials tungsten chloride and urea in anhydrous ethanol at a ratio of 0.08-0.1:0.8-1, and subjecting the mixed solution to magnetic stirring at 10°C-40°C until the raw materials are completely dissolved in the anhydrous ethanol, and then titrating the dissolved solution with deionized water and continuing to subject the mixed solution to magnetic stirring until the mixed solution becomes colorless and transparent; S2: The mixed solution obtained in S1 is quickly poured into a polytetrafluoroethylene liner and then transferred into a hydrothermal reactor. The sealed reactor is placed in a drying oven and dried and kept warm for a period of time, thereby performing a hydrothermal reaction to synthesize the product; S3: After natural cooling, the precipitate is ultrasonically dispersed and centrifuged with deionized water. The washed product is dispersed in deionized water to form a dispersion. The dispersion is placed in a freeze dryer to remove the deionized water to directly obtain a highly dispersible blue-gray WO 2.72 .
2. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to claim 1 2.72 The method for preparing nanospheres is characterized in that: The magnetic stirring rate is 100-500 rpm, the stirring time is 2-6 hours, the amount of deionized water added is 0.5-1.5 parts, and the amount of ethanol is 60-100 parts.
3. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to claim 2 2.72 The method for preparing nanospheres is characterized in that: During the magnetic stirring in S1, the magnetic stirring rate was 300 rpm, the stirring time was 3 hours, the amount of deionized water added was 0.9 parts, and the amount of ethanol added was 80 parts.
4. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to claim 1 2.72 The method for preparing nanospheres is characterized in that: During the drying in S2, the drying temperature is 100-250° C. and the heat preservation time is 8-30 hours.
5. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to claim 4 2.72 The method for preparing nanospheres is characterized in that: During the drying in S2, the drying temperature is 180° C. and the heat preservation time is 18 hours.
6. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to claim 1 2.72 The method for preparing nanospheres is characterized in that: In S3, the ultrasonic dispersion time is 5-20 min, the number of ultrasonications is 5-10 times, the centrifuge speed is 6000-10000 rpm, the number of centrifugations is 5-10 times, the temperature of the freeze dryer is -60°C-0°C, the air pressure in the freeze dryer is 0.1-5 Pa, and the freeze drying time is 10-48 hours.
7. The oxygen-deficient tungsten oxide WO having photodegradation adsorption performance according to any one of claims 1 to 4 2.72 Preparation method of nanospheres to prepare oxygen-deficient tungsten oxide WO 2.72 Application in environmental governance and energy conversion.
8. The use according to claim 7, characterized in that The following steps are involved: S1: First determine the concentration of methylene blue in the contaminated water source by spectrophotometer. If it is less than 50 mg / L, the WO 2.72 The concentration in the solution is 25 mg / L; if it is higher than 50 mg / L, the WO 2.72 The concentration in the solution is 50 mg / L. The corresponding WO is taken according to the amount of sewage to be treated. 2.72 The amount of S2: WO determined according to S1 2.72 The amount of the methylene blue was weighed, dispersed in deionized water, and the dispersion was poured into a nanofiltration membrane for sealing, and then put into a water source pool contaminated by methylene blue; S3: Based on S2, the used WO 2.72 Desorption and recovery treatment is carried out; each time the used WO 2.72 The amount of desorption does not exceed 3g, and the amount of all solvents used is 100ml; the desorption recovery mainly includes the following steps: S3.1: Used WO 2.72 Place in 100 ml of deionized water for 30 min ultrasonic dispersion, and then magnetically stir for 4 h to make WO 2.72 The attached materials on WO were dissolved in deionized water. 2.72 Desorption was performed, and the above steps were repeated twice, followed by centrifugation at 8000 rpm, and the aqueous solution after centrifugation was collected, and WO was recovered at the same time. 2.72 ; S3.2: WO recovered by centrifugation 2.72 Disperse it again in 100 ml of deionized water and add 50 times of sodium chloride to make the sodium ions react with WO 2.72 The attached substances on the WO are exchanged by ions, and the replaced adsorbents are dissolved in deionized water to achieve the purpose of WO 2.72 Continuous desorption; S3.3: Centrifuge the recovered WO again 2.72 Dispersed in 100 ml of organic solvent ethanol, ethanol to make WO 2.72 Dissolve the attachments on WO 2.72 Further desorption is performed; S4: WO 2.72 After three desorption cycles, WO 2.72 Dispersed in deionized water, freeze-dried, freeze-dried at -45 °C, 0.5 Pa pressure, freeze-dried for 36 hours, and collected desorbed WO after freeze-drying. 2.72 , to be used again for photodegradation and adsorption of the dye methylene blue.
9. The use according to claim 8, characterized in that In S2, the water source is sampled every 2.5 hours during the day and every 5 hours at night, and the sampling interval can be adjusted according to the concentration change of methylene blue; the absorbance corresponding to the characteristic wavelength is measured by a spectrophotometer until the concentration of methylene blue in the water source drops to the concentration of the added WO 2.72 If the removal limit meets the discharge requirements, the adsorption and photodegradation of methylene blue will be stopped; if it does not meet the requirements, the WO2-containing solution will be added to the polluted water source. 2.72 Nanofiltration membranes for deionized water dispersions.
10. The use according to claim 8, characterized in that In S3, the desorption steps are: ultrasonic dispersion, magnetic stirring, centrifugal recovery. The specific parameters are the same as above, the number of cycles is 2, and the solution after centrifugation is continuously collected and the used WO is recovered. 2.72 .
Citation Information
Patent Citations
Preparation method of filament-like W18O49 material
CN105236491A
Nanowire cluster WO3-W18O49 heterojunction membrane sensitive to ammonia gas
CN107831194A
Oxygen-deficiency type tungsten trioxide nanosheet adsorbent and preparation method thereof
CN109364871A
WO<2.72> nanorod composite material covered by polyaniline, and preparation method and application of WO<2.72> nanorod composite material
CN110773238A
Method for preparing W18O49 / WO3 heterogeneous electrocatalyst by utilizing oxygen deficiency, electrocatalyst and application
CN116081691A
